A new three‐dimensional cadmium(II) coordination polymer based on bis[4‐(2‐methylimidazol‐1‐yl)phenyl]methanone: synthesis, structure and properties. Issue 2 (31st January 2022) - Sun, Yao; Li, Ke; Xu, Dan-Ni; Chen, Jia-Jia; Wang, Xin-Yu; Xu, Xiao-Juan; Tao, Jian-Qing
Abstract : A cadmium(II) compound, prepared by reaction of Cd(NO3 )2 ·6H2 O with benzene‐1, 4‐diacetic acid and bis[4‐(2‐methylimidazol‐1‐yl)phenyl]methanone in a mixture of H2 O and dimethylformamide, possesses a new three‐dimensional pillar–layer framework based on Cd II –PBEA layers and MIPMO pillars, which can be simplified into a pcu topological network. The title compound displays a highly selective and sensitive sensing for Fe 3+ ions in aqueous solution. In addition, it displays a high photocatalytic activity for the degradation of methylene blue (MB) in water under UV light irradiation. Abstract : A novel three‐dimensional Cd II coordination polymer, namely, poly[[(μ3 ‐benzene‐1, 4‐diacetato)(μ2 ‐benzene‐1, 4‐diacetato)bis{μ2 ‐bis[4‐(2‐methylimidazol‐1‐yl)phenyl]methanone}dicadmium(II)] tetartohydrate], {[Cd(C10 H8 O4 )(C21 H18 N4 O)]·0.25H2 O} n or {[Cd(PBEA)(MIPMO)]·0.25H2 O} n, (I), was synthesized by the hydrothermal method using benzene‐1, 4‐diacetic acid (H2 PBEA), bis[4‐(2‐methylimidazol‐1‐yl)phenyl]methanone (MIPMO) and Cd(NO3 )2 ·6H2 O. The title compound was structurally characterized by single‐crystal X‐ray diffraction, elemental analysis, IR spectroscopy and thermogravimetric analysis, and exhibits a three‐dimensional pillar–layer framework based on Cd II –PBEA layers and MIPMO pillars, which can be simplified into a pcu topological network. The title compound displays a highly selective and sensitive sensing for Fe 3+ ions in aqueous solution. In addition, it displays a high photocatalytic activity for the degradation of methylene blue (MB) in water under UV light irradiation.